2007
DOI: 10.1161/circulationaha.106.678979
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Techniques Disproportionately Benefit Women and Narrow the Gender Disparity in Outcomes After Coronary Artery Bypass Surgery

Abstract: Background-Women experience greater morbidity and mortality than men after conventional coronary artery bypass grafting (CABG) on cardiopulmonary bypass (CPB). The objective of this study was to determine whether off-pump CABG (OPCAB) alters this gender-based disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 34 publications
3
58
0
3
Order By: Relevance
“…(14) while the late mortality did not differ compared to conventional surgery (42). Several retrospective studies found a benefit in using off-pump techniques in other high risk groups such as: females (43) or reoperative coronary artery bypass grafting (44). Overall, the weight of randomized data for the high risk patient undergoing coronary surgery shows a clear benefit from OPCAB as demonstrated by other landmark retrospective studies (45) or large meta-analyses of nonrandomized trials (46) ( Table 9).…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 86%
“…(14) while the late mortality did not differ compared to conventional surgery (42). Several retrospective studies found a benefit in using off-pump techniques in other high risk groups such as: females (43) or reoperative coronary artery bypass grafting (44). Overall, the weight of randomized data for the high risk patient undergoing coronary surgery shows a clear benefit from OPCAB as demonstrated by other landmark retrospective studies (45) or large meta-analyses of nonrandomized trials (46) ( Table 9).…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 86%
“…Disagreements were resolved through consensus. Eleven authors were contacted by e-mail (up to three attempts per author) for additional information, including confirmation that there were no duplicate data and clarification of the AKI definition used in trials (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Five authors provided additional information (25,29,30,32,33).…”
Section: Data Abstractionmentioning
confidence: 99%
“…10 OPCAB has been shown to be beneficial for patients at increased risk of stroke, diabetic patients, and women. [11][12][13][14][15] In particular, we have previously demonstrated a significant early mortality and morbidity advantages for women and equal 10-year survival compared with men. 12 Specifically, among OPCAB patients, we have previously reported the mitigation of adverse events and equalization of outcomes in women compared with men.…”
mentioning
confidence: 96%
“…12 Specifically, among OPCAB patients, we have previously reported the mitigation of adverse events and equalization of outcomes in women compared with men. 14 The present study seeks to determine whether the disproportionate advantage of OPCAB observed in 1 high-risk demographic group (women) may also be present for another identifiable high-risk demographic group (blacks).…”
mentioning
confidence: 99%